Out where the west begins : profiles, visions & strategies of early western business leaders - Anschutz, Philip; Convery, William Joseph; Noel, Thomas J., (Thomas Jacob) (Denver, Colorado : Cloud Camp Press, LLC, 2015)
Between 1800 and 1920, an extraordinary cast of bold innovators and entrepreneurs--individuals such as Cyrus McCormick, Brigham Young, Henry Wells and James Fargo, Fred Harvey, Levi Strauss, Adolph Coors, J. P. Morgan, and Buffalo Bill Cody--helped lay the groundwork for what we now call the American West. They were people of imagination and courage, adept at maneuvering the rapids of change, alert to opportunity, persistent in their missions. They had big ideas they were not afraid to test. They stitched the country together with the first transcontinental railroad, invented the Model A and built the roads it traveled on, raised cities and supplied them with water and electricity, established banks for immigrant populations, entertained the world with film and showmanship, and created a new form of western hospitality for early travelers. Not all were ideal role models. Most, however, once they had made their fortunes, shared them in the form of cultural institutions, charities, libraries, parks, and other amenities that continue to enrich lives in the West today. Out Where the West Begins profiles some fifty of these individuals, tracing the arcs of their lives, exploring their backgrounds and motivations, identifying their contributions, and analyzing the strategies they developed to succeed in their chosen fields. Working with western scholars William J. Convery and Thomas J. Noel, Anschutz has brought a unique perspective to his subject in this engaging book of essays--Tattered Cover Bookstore summary, edited from book jacket.
Manuel Lisa -- William Henry Ashley -- John Jacob Astor -- Charles and William Bent and Ceran St. Vrain -- Brigham Young -- Cyrus H. McCormick -- Charles Goodnight -- John Wesley Iliff -- Charles Boettcher -- Henry Miller -- Frederick Weyerhaeuser -- Henry Wells and William Fargo -- John Evans -- Benjamin Holladay -- The big four: Collis P. Huntington, Mark Hopkins, Jr., Leland Stanford, Charles Crocker -- Thomas C. Durant -- Cyrus K. Holliday -- Theodore D. Judah -- George Mortimer Pullman -- William Jackson Palmer -- James J. Hill -- Fred Harvey -- Henry E. Huntington -- Meyer Guggenheim -- Nathaniel P. Hill -- John D. Rockefeller, Sr. -- Edward L. Doheny -- George Hearst -- Spencer Penrose -- Samuel Colt -- Levi Strauss -- G. F. Swift -- Andrew Carnegie -- Charles A. Pillsbury -- Adolph Coors -- Henry Ford -- Jay Cooke -- Walter Scott Cheesman -- A. P. Giannini -- J. P. Morgan -- Harrison Gray Otis -- Carl Laemmle -- Buffalo Bill Cody.
Includes bibliographical references and index.
Keywords: 1800-1899; Businessmen -- West (U.S.) -- 19th century -- Biography; Entrepreneurship -- History -- West (U.S.) -- 19th century; Industrialization -- History -- West (U.S.) -- 19th century; BIOGRAPHY & AUTOBIOGRAPHY / Business; BUSINESS & ECONOMICS / Entrepreneurship; BUSINESS & ECONOMICS / Leadership; HISTORY / United States / 19th Century; HISTORY / United States / 20th Century; Businessmen; Entrepreneurship; Industrialization; West (U.S.) -- 19th century -- History; West United States; Biographies; History; Biographies; Biography; Nonfiction; Biographies